Karta i︠u︡zhnoĭ chasti Tatarskago proliva ot mysa Tumannago do mysa Mosolova sostavlena po gidrograficheskimʺ i topograficheskimʺ rabotamʺ chinov Morskogo i Voennago Vi︠e︡domstvʺ sʺ 1879 - 1900 g.g. Izdana Glavnymʺ Gidrograficheskimʺ Upravlenīemʺ vʺ 1902 g. / Kopirovalʺ khimich. tushʹi︠u︡ N. Zherebit︠s︡ovʺ - Russia. Glavnoe gidrograficheskoe upravlenīe; (Sankt-Peterburg : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; [Санкт-Петербург] : Морское министерство, Главное гидрографическое управленіе, 1902)
Relief shown by hauchers. Depths shown by soundings and isolines.; Title translation: Map of the southern part of the Tatar Strait from Cape Tumanny to Cape Mosolov compiled based on the hydrographic and topographic works of the naval and military departments from 1879 - 1900.; Top margin title translation: Eastern Sea.; Greenwich meridian.; Includes inset map.; Inset map: "Plan bukhty Soni po rabotam kanoner. lodki Sivuch v 1889 g." = Plan of Soni Bay according to the work gun boat Sibuch in 1889.; "Masshtabʺ 6 milʹ vʺ di︠u︡ĭmi︠e︡ (1/438480)" = Scale 6 miles in 1 inch (1/438480).; "No. 589" -- bottom right margin Color; 1:438,480